2015
DOI: 10.1371/journal.pone.0141592
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Hymenoscyphus albidus and H. fraxineus on Fraxinus excelsior and F. pennsylvanica

Abstract: European ash (Fraxinus excelsior) is currently battling an onslaught of ash dieback, a disease emerging in the greater part of its native area, brought about by the introduction of the ascomycete Hymenoscyphus fraxineus (= Hymenoscyphus pseudoalbidus). The closely-related fungus Hymenoscyphus albidus, which is indigenous to Europe, is non-pathogenic when in contact with F. excelsior, but could pose a potential risk to exotic Fraxinus species. The North American green ash (Fraxinus pennsylvanica) is planted wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 42 publications
1
45
0
1
Order By: Relevance
“…All tested species except F. profunda developed relatively long lesions in the direct stem inoculation experiment (short in F. profunda), supported pathogen sporulation and showed generally high levels of pathogen DNA in leaf tissues. Other studies have similarly reported moderate susceptibility to ash dieback in species from section Melioides (Drenkhan and Hanso 2010;Gross and Sieber 2016;Kowalski et al 2015). The moderate disease susceptibility of North American ash species provides further support for the presence of an ancient phylogenetic signal in terms of pathogen host range.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…All tested species except F. profunda developed relatively long lesions in the direct stem inoculation experiment (short in F. profunda), supported pathogen sporulation and showed generally high levels of pathogen DNA in leaf tissues. Other studies have similarly reported moderate susceptibility to ash dieback in species from section Melioides (Drenkhan and Hanso 2010;Gross and Sieber 2016;Kowalski et al 2015). The moderate disease susceptibility of North American ash species provides further support for the presence of an ancient phylogenetic signal in terms of pathogen host range.…”
Section: Discussionsupporting
confidence: 57%
“…Based on observations from Estonian parks, F. nigra seems to be highly susceptible to shoot infection, while F. americana and F. pennsylvanica are more tolerant (Drenkhan and Hanso 2010). Inoculation studies have further shown that F. pennsylvanica develops minor lesions after stem inoculation with H. fraxineus (Gross and Sieber 2016;Kowalski et al 2015). North American Fraxinus species are already severely threatened by the introduced emerald ash borer (Kovacs et al 2010).…”
Section: Potential Consequences Of An Introduction Of H Fraxineus Tomentioning
confidence: 99%
“…Both measures of symptom development were highly correlated with in vitro growth rate (Table 1b, Figure 1b). The present assay on seedlings took 28 days, which is considerably faster than previously reported experiments on this pathosystem (Kowalski et al, 2015;Schwanda & Kirisits, 2016). The overall preparation time for the assay was therefore reduced from about 6 weeks to about 7 days.…”
Section: Re Sults and Discussionmentioning
confidence: 74%
“…The method avoids the use of ash wood sticks, which requires availability of a suitable wood source and time to make, autoclave and inoculate the sticks. It also allows statisti- (Kowalski et al, 2015). The present assay on seedlings took 28 days, which is considerably faster than previously reported experiments on this pathosystem (Kowalski et al, 2015;Schwanda & Kirisits, 2016).…”
Section: Re Sults and Discussionmentioning
confidence: 78%
“…The ability of the fungus to produce necrotic lesions after artificial stem wound inoculation has been demonstrated on F. angustifolia, F. excelsior, F. mandshurica var. japonica and F. pennsylvanica (Bakys et al, 2009;Kirisits et al, 2010;Husson et al, 2011;Gross & Holdenrieder, 2015;Kowalski et al, 2015;Gross & Sieber, 2016). The present study has confirmed the high pathogenicity of H. fraxineus towards F. excelsior.…”
Section: Discussionmentioning
confidence: 99%